SISTEM MUTU AKUNTANSI PADA SMP ISLAM DONOMULYO : Sistem, Mutu, Akuntansi Keuangan - Isnaeni, Diana; Hariono, Jefri (JUMBA (Jurnal Manajemen, Bisnis, dan Akuntansi), 2022)
This study aims to develop a quality system for financial accounting and human resource management at Donomulyo Islamic Middle School.Design Based Research method with the following steps: (1) Identification of Problems (2) Identification of Objectives (3) Preparation of Product Design (4) Product Design Test (5) Evaluation of Product Design Test Results (6) Product Communication. The subject used was Donomulyo Islamic Middle School, the data obtained through observation and interviews, and questionnaires. Questionnaire answers using a Likert scale with 5 rating categories (1) Very Inadequate, (2) Inadequate, (3) Adequate Enough, (4) Eligible, (5) Very Eligible. The data analysis technique uses the percentage of quality systems tested by two validators, academics and practitioners.The results of this study are the accounting quality system at Donomulyo Islamic Middle School finance with the following specifications: vision, mission, goals, organizational structure, job description, quality policy and SOP (Standard Operating Procedure).